ANALISIS AKUNTABILITAS, EFEKTIVITAS DAN EFISIENSI PENGELOLAAN ALOKASI DANA DESA DALAM UPAYA PEMERATAAN PEMBERDAYAAN MASYARAKAT (Studi di Desa Pucangarum Kecamatan Baureno Kabupaten Bojonegoro) - Ahmad Khoirul Imaduddin; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine and analyze the Accountability, Effectiveness and Efficiency of Village Fund Allocation Management in Efforts to Equalize Community Empowerment (Study in Pucangarum Village, Baureno District, Bojonegoro Regency). The type of research used is qualitative research with descriptive statistical data analysis methods. Data was collected by using observation, interview, and documentation techniques. The results showed that (1) the planning stage of the Village Fund Allocation (ADD) in the village of Pucangarum was in accordance with what was planned by the village government and in accordance with the needs of the community to improve the standard of living of the community (2) the administration of the management of the allocation of village funds in the village of Pucangarum as the manager has tried his best and has referred to Permendagri No. 20 of 2018 from planning to accountability, and for the recording process it is in accordance with the provisions of the law. (3) Accountability for Village Fund Allocation (ADD) in Pucangarum Village with transparency or openness by the village government as ADD manager to the community in the form of information on the use of ADD funds so that positive prejudices arise from village communities towards village officials.”Keywords: Accountability, Effectiveness, Village Fund Allocation (ADD), Community